Membrane biology: disentangling cellular lipid connections - Brügger, Britta (Current biology, 2020)
Biological membranes consist of a surprisingly high number of different lipid species. Little is known about how individual lipids cooperate in modulating cellular functions. A new study suggests an intricate interplay of sphingolipids with ether lipids in vesicular transport.
Gesehen am 12.11.2020